ANALISIS KINETIKA DEPOSISI LAPISAN TIPIS ZNO YANG DITUMBUHKAN DENGAN METODE METALORGANIC CHEMICAL VAPOR DEPOSITION DAN METODE ATOMIC LAYER DEPOSITION - Setiawan (NIM 20296501), Agus
Abstract : In this study, models of deposition mechanism of ZnO thin film grown by metalorganic chemical vapor deposition (MOCVD) and atomic layer deposition (ALD) methods using dietylzinc (DEZ) and H2O as reactants were constructed. The models were used to obtain information on the relationship among deposition rate as experiment parameters, such as substrate temperature, temperature of DEZ bubbler, and temperature of H2O bubbler. The proposed models are able to explain precisely the experiment data. Analysis on the self limiting mechanism phenomenon in the ALD-ZnO process was also performed. Moreover, effects of ultra violet irradiation in MOCVD-ZnO process were also studied.